Peningkatan Minat Belajar Pai Melalui Diskusi Kelompok Pada Siswa Kelas 4 SDN 06 Pancung Soal - Vemi Sherly Afni (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ interest and learning outcomes in Islamic Education (PAI) subjects through the implementation of Project-Based Learning (PjBL). The research subjects were 12 fourth-grade students at SDN 06. The study was conducted in two cycles, consisting of planning, implementation, observation, and reflection phases. The results showed an increase in students’ learning interest from Cycle I to Cycle II. In Cycle I, students’ learning interest was categorized as moderate, but in Cycle II, it improved significantly to a very high category, with an average achievement of 83.3%. The implementation of this method proved effective in enhancing students’ engagement, learning outcomes, and interest in PAI, particularly in the topic of Friday prayer. These findings support constructivist learning theories, emphasizing the importance of hands-on experiences and group discussions in education